Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Biro Administrasi Pembangunan Dan Layanan Pengadaan Jasa Pemerintah Provinsi Maluku - Aldrin Usmany; Sherly Rutumalessy; Kalsum Lussy (P3M Politeknik Negeri Ambon, 2024)
Initial survey on the Influence of Work Discipline on the Performance of Employees of the Development Administration Bureau and Maluku Provincial Government Procurement Services. Shows there are problems with employee discipline and performance. This lack of employee discipline will certainly have an impact on performance. Working less than normal hours will result in work not being completed on time or things not being completed. This can be proven through recapitulation of performance achievement data. The analytical method used in this research is quantitative analysis and simple linear regression analysis. Quantitative analysis in the Likert scale range of 1 to 5 shows that employee discipline affects the performance of employees of the Development Administration Bureau and government services procurement services in Maluku Province. Shows there are problems with employee discipline and performance. On the Performance of Development Administration Bureau Employees and Maluku Provincial Government Service Procurement Services. Shows there are problems with employee discipline and performance. has an average value of 0.785 which is interpreted as quite good, while employee performance has an average value of 0.731 which is interpreted as quite good. The results of the hypothesis test of the discipline variable (X) on employee performance (Y) show a calculated t value of 4.258. So it can be concluded that discipline has a positive effect on employee performance. The influence of the independent variable on the dependent variable (employee performance) Based on these results, it can be concluded that the better the discipline, the better the performance of disciplined employees regarding the performance of employees of the Development Administration Bureau and government services procurement services in Maluku Province. Shows there are problems with employee discipline and performance. To improve it, leaders need to pay attention. Supervise each employee regarding discipline regarding performance. Keywords: Discipline, Employee Performance